Regional distribution in Spain of the agricultural aid by the World Trade Organization (2002-2010) - González-Moralejo, Silvia Andrés; García Álvarez-Coque, José María (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The Common Agricultural Policy (CAP) defines, structure and allocates subsidies to agricultural production in the European Union. The CAP is subject to the guidelines of the World Trade Organization (WTO), especially after the Agriculture Agreement (1994). This work aims to determine the regional distribution of domestic support received from the CAP in Spain and their classification according to the methodology of the WTO. Domestic support is associated with WTO compartments: green box, blue and amber. It analyzes and compares the evolution of the boxes, to infer the current situation of Spain and its adaptation to WTO rules. The results suggest that Spain is gradually adapting to the WTO agricultural criteria, but at a slow pace: growing the green box and reduces the blue and amber, but in some regions the green box still represents only a small percentage of the total.